Canadian Gallup Poll, September 1985, #501_1 - Gallup Canada (Borealis, 2019)
This Gallup poll seeks the opinions of Canadians, on both political and social issues. The questions ask opinions about the Northwest Passage and other political issues within the country. There are also questions on other topics of interest and importance to the country and government, such as homosexuality, aids and the death penalty. The respondents were also asked questions so that they could be grouped according to geographical variables. Topics of interest include: allowing a high speed police chase; the amount of homosexuals today; the causes of homosexuality; changes in the safety of air travel; controlling the Northwest passage; ideas about romance; the individuals who are most at risk for getting aids; knowledge of aids; the knowledge of the U.S. icebreaker in the Northwest Passage; the level of romance today, compared to the past; the location of summer holidays; the number of people who die from aids; rating safety records of major airlines; the satisfaction with airline safety procedures; spreading aids; supporting the death penalty; taking summer holidays; the United State's influence over the Canadian culture; what romance means; and who should be the head of state. Basic demographic variables are also included.